(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article presents an analysis of the process of subordination of artistic thinking to ideological dictates, «inscribing» the literary practice of the subject of aesthetic creativity in the format of a single Soviet method. It is proved that at the stage of political structuring of literary and artistic life, strengthening of regulation and unification of creativity, writers in the format of socialist realism are forced to use new tactics and methods, to find ways of adapting.